Functional and pharmacological properties of triheteromeric GluN1/2B/2D NMDA receptors. (2nd November 2019) - Yi, Feng; Bhattacharya, Subhrajit; Thompson, Charles M.; Traynelis, Stephen F.; Hansen, Kasper B.
Abstract : Key points: Triheteromeric NMDA receptors contain two GluN1 and two distinct GluN2 subunits and mediate excitatory neurotransmission in the CNS. Triheteromeric GluN1/2B/2D receptors have functional properties intermediate to those of diheteromeric GluN1/2B and GluN1/2D receptors. GluN1/2B/2D receptors are more sensitive to channel blockade by ketamine and memantine compared to GluN1/2B receptors in the presence of physiological Mg 2+ . GluN2B‐selective antagonists produce robust inhibition of GluN1/2B/2D receptors, and the GluN2B‐selective positive allosteric modulator spermine enhances responses from GluN1/2B/2D but not GluN1/2A/2B receptors. These insights into the properties of triheteromeric GluN1/2B/2D receptors are necessary to appreciate their physiological roles in neural circuit function and the actions of therapeutic agents targeting NMDA receptors. Abstract: Triheteromeric NMDA‐type glutamate receptors that contain two GluN1 and two different GluN2 subunits contribute to excitatory neurotransmission in the adult CNS. In the present study, we report properties of the triheteromeric GluN1/2B/2D NMDA receptor subtype that is expressed in distinct neuronal populations throughout the CNS. We show that neither GluN2B, nor GluN2D dominate the functional properties of GluN1/2B/2D receptors because agonist potencies, open probability and the glutamate deactivation time course of GluN1/2B/2D receptors are intermediate to those of diheteromeric GluN1/2B and GluN1/2D receptors. Furthermore, channel blockade of GluN1/2B/2D by extracellular Mg 2+ is intermediate compared to GluN1/2B and GluN1/2D, although GluN1/2B/2D is more sensitive to blockade by ketamine and memantine compared to GluN1/2B in the presence of physiological Mg 2+ . Subunit‐selective allosteric modulators have distinct activity at GluN1/2B/2D receptors, including GluN2B‐selective antagonists, ifenprodil, EVT‐101 and CP‐101‐606, which inhibit with similar potencies but with different efficacies at GluN1/2B/2D (∼65% inhibition) compared to GluN1/2B (∼95% inhibition). Furthermore, the GluN2B‐selective positive allosteric modulator spermine enhances responses from GluN1/2B/2D but not GluN1/2A/2B receptors. We show that these key features of allosteric modulation of recombinant GluN1/2B/2D receptors are also observed for NMDA receptors in hippocampal interneurons but not CA1 pyramidal cells, which is consistent with the expression of GluN1/2B/2D receptors in interneurons and GluN1/2A/2B receptors in pyramidal cells. Altogether, we uncover previously unknown functional and pharmacological properties of triheteromeric GluN1/2B/2D receptors that can facilitate advances in our understanding of their physiological roles in neural circuit function and therapeutic drug actions. Key points: Triheteromeric NMDA receptors contain two GluN1 and two distinct GluN2 subunits and mediate excitatory neurotransmission in the CNS. Triheteromeric GluN1/2B/2D receptors have functional properties intermediate to those of diheteromeric GluN1/2B and GluN1/2D receptors. GluN1/2B/2D receptors are more sensitive to channel blockade by ketamine and memantine compared to GluN1/2B receptors in the presence of physiological Mg 2+ . GluN2B‐selective antagonists produce robust inhibition of GluN1/2B/2D receptors, and the GluN2B‐selective positive allosteric modulator spermine enhances responses from GluN1/2B/2D but not GluN1/2A/2B receptors. These insights into the properties of triheteromeric GluN1/2B/2D receptors are necessary to appreciate their physiological roles in neural circuit function and the actions of therapeutic agents targeting NMDA receptors.